An overview of the Opisthonema oglinum (Lesueur, 1818) fishery in Caponga, Cascavel county, Ceará State, Brazil - Sá, Geny Gil; Marinho, Reynaldo Amorim; Conceição, Raimundo Nonato de Lima (Arquivos de Ciências do Mar, 2012)
This research project was carried out through surveying visits made to Caponga Beach in the period from April to October, 2010. Data were collected for the description of the fishing for Atlantic thread herring, Opisthonema oglinum, characterization of the fishing grounds and knowledge of the trade exerted by fishermen and middlemen. Catch data were also made available on the sardine fishery production in the period 2001 to 2008. This species represented 8.6% of the total production of fish obtained on the coastal areas of Ceará State in 2006, having reached 30.4 t of the total fish landed in Cascavel county. The fishery is carried out by small sailing crafts that operate mainly with gill nets. In spite ob being one of the most important species caught in small-scale fisheries in the region, studies of the Atlantic thread herring are still scarce. The commercialization of the production follows several trade paths, from fishermen and/or boat owners to brokers, restaurants and consumers. Fishing for the Atlantic thread herring occurs daily throughout the year in Caponga Beach and such a scenario can lead to a disorderly exploitation to the extent that high fishing pressures has been constantly exerted on its stocks.